APOBEC enzymes: mutagenic fuel for cancer evolution and heterogeneity - Swanton, Charles (Cancer Discov, 2015)
Deep sequencing technologies are revealing the complexities of cancer evolution, casting light on mutational processes fuelling tumor adaptation, immune escape, and treatment resistance. Understanding mechanisms driving cancer diversity is a critical step toward developing strategies to attenuate tumor evolution and adaptation. One emerging mechanism fuelling tumor diversity and subclonal evolution is genomic DNA cytosine deamination catalyzed by APOBEC3B and at least one other APOBEC family member. Deregulation of APOBEC3 enzymes causes a general mutator phenotype that manifests as diverse and heterogeneous tumor subclones. Here we summarise knowledge of the APOBEC DNA deaminase family in cancer, and their role as driving forces for intratumor heterogeneity and a therapeutic target to limit tumor adaptation.